Effect of feed supplement modifications using keratinolytic bacteria on growth performance and meat chemical composition of domesticated quail - PRASETYO, ENDRY NUGROHO; HIDAYAT, MUHAMMAD TAUFIQ; KOENTJORO, MAHARANI PERTIWI (The Indian Journal of Animal Sciences, 2023)
This study was carried out to determine a novel strategy for utilization of feather in poultry feed, along with the addition of immobilized keratinolytic Bacillus sp. SLII–1 as a supplement. Eighty male quails (day–old) were randomly divided into four diet groups, with each group receiving four different treatments. The results showed that Bacillus sp. SLII–I exhibited keratinolytic potential by increasing the protein solubility of feather meal in a liquid medium. The immobilization of Bacillus sp. SLII–I using 3% sodium alginate and 0.8% chitosan composition occurred at approximately 4.05×107 CFU/g, while the viable cells were maintained in acidic medium (pH 3.0) at around 3.95×107 CFU/g. Quails aged 19–33 days, fed with feather meal and Bacillus sp. SLII–1, demonstrated significantly higher weight gain and lower feed conversion ratio (FCR) as compared to those treated with feather meal without supplements. There were no significant differences in the values of dry matter, ash, and crude protein content of the meat among the quails in all the treatments. Therefore, feed supplemented with immobilized bacteria and feather waste can be utilized as an alternative diet for quails. This way, the use of feed materials can be reduced, and at the same time, chicken feather waste can be effectively utilized.